The secularisation of religious education: humanism, religion and worldview education in the Netherlands in the 1960s. Issue 2 (3rd May 2016) - Stolk, Vincent; Gasenbeek, Bert; Veugelers, Wiel
Abstract: Secularisation is often mentioned as an explanation for changes in worldview education in modern history. Worldview education has become less preoccupied with preaching religious truths and more with developing children's personal worldviews. However, how secularisation exactly explains these changes is not clear. To get a clearer picture, we analyse developments in the Netherlands in the 1960s and compare these with Britain. Our source material primarily consists of educational, religious and humanist journals. We connect developments in worldview education to secularisation understood in three ways: reduced church attachment, the rise of alternatives to the dominant religion, and the decrease in references to religion in public space. Our findings show that changes in theology, decline in church attendance, professionalisation of academic pedagogy, and the growing popularity of dialogical methods strongly influenced the direction of both religious and humanist forms of worldview education in a similar way.